The practice of war production, reproduction and communication of armed violence - Rao, Aparna; Bollig, Michael; Bock, Monica (Berghahn Books, 2007)
Provides information to help in a better understanding of the specific and the general in wartime. This book examines how people cope and adjust to situations of war, depending upon whether these are low-intensity or high-intensity ones, and on whether they are brief phases of conflict or long enduring periods of violence.